Sejarah Akuntansi Dan Perkembangan Akuntansi Di Era Revolusi Industri 4.0 - Hasna Huwaidah; Shofie Huwaidah; Fani Alviyanto; Gunawan Aji (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Accounting is a means of resolving social conflicts, a tool for fostering constructive dialogue between members of society, and an institutional mechanism for resolving problems, carrying out evaluations, and fostering understanding within a social network. The aim of this research is to find out the history of accounting and the role of accountants in digital transformation in the Industry 4.0 era. The method used in this research is a bibliographic approach sourced from books and scientific journals that are relevant to the topic and focus of the research. This research uses a descriptive qualitative approach in the form of an explicit literature review. The findings from this research show that the role of accountants in the industrial revolution is still relevant as digital consultants with several skills and certifications. Much technical infrastructure has been created as the world moves towards industrial revolution 4.0. Therefore, new research into these latest developments is needed to verify that accountants are qualified to carry out their duties in the era of revolution 4.0.